Consequences analysis for storage explosive - Saiful Azhar, Saad; Abdul Rahman, M.; Saari, Mustapha; Farizul Hafiz, Kasim; Suhardy, Daud (Universiti Malaya, 2010)
Organized by Universiti Malaya, 16th - 17th May 2006 at Crystal Crown Petaling Jaya, Malaysia.